2020
DOI: 10.1186/s12891-020-3043-9
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of three or more lumbar discs significantly decreases lumbar spine/hip ROM ratio during position change from standing to sitting in AVN patients before THA

Abstract: Background: Limitations in the lumbar spine movement reduce lumbar vertebral motion and affect spinopelvic kinematics. We studied the influence of lumbar intervertebral disc degeneration on spinofemoral movement, from standing to sitting, in patients undergoing total hip arthroplasty (THA). Methods: Of 138 consecutive patients scheduled for THA due to unilateral avascular necrosis (AVN) of the femoral head, those with ≥3 discs with University of California at Los Angeles (UCLA) disc degeneration score > 1 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…There were remarkable associations among spine, pelvis, and hip joints, namely compensatory mechanism in previous studies [17][18][19] . Moreover, those associated effects were notable during position changing 20,21 .…”
Section: Introductionmentioning
confidence: 82%
“…There were remarkable associations among spine, pelvis, and hip joints, namely compensatory mechanism in previous studies [17][18][19] . Moreover, those associated effects were notable during position changing 20,21 .…”
Section: Introductionmentioning
confidence: 82%
“…Other works give more information regarding how not only the timing of the operations but also the range of lumbar fusions can affect the dislocation rate. It is estimated that the dislocation rate for THR patients without prior spinal fusion was 2.4%, 4.3% for patients with one to two levels fused, and 7.5% for patients with three to five levels fused [40].…”
Section: Discussionmentioning
confidence: 99%
“…There were significant connections among spine, pelvis, and hip joints during position changes in healthy human beings 10,11 and patients with spine or hip joints disorders [33][34][35] . A previous study 16 demonstrated that sagittal acetabular version would change significantly after PSO at lumbar spine.…”
Section: Discussionmentioning
confidence: 99%